Pedagogical Relevance of Irresistible Lexical Items Used in Online Media: A Case Study of Urdu Speakers, India - Dedy Suhery; Mohd Hamid Raza; M. Yusuf Hasbalnikistan (JADEs Journal of Academia in English Education, 2024)
This paper attempts to determine the account of the irresistible lexical items used in online media, examine the pedagogical strategies that impacted the cycle of the psychological expressions, and generalize the media's applications attracted to the learners' intentions through the features of irresistible lexical items. The researchers used qualitative descriptive with several techniques, including collecting data from Urdu speakers (participants) who used the irresistible lexical items in language teaching. And then, after reading newspapers, magazines, gadgets, books, journals, etc., the researchers generalized the ideas and concepts of the learners. The account of the irresistible lexical items' pedagogical relevance in online media could improve the Urdu speakers and affect the pedagogical levels, particularly in speaking. The pedagogical structure shapes the teachers' actions, judgments, and other teaching strategies and considers the learners' needs, backgrounds, and understanding. In addition, Language teaching adopts the linguistic framework of the lexical items and affects the medium of communication. Even similar words may be present in its language, affecting the pedagogical structure of language teaching.